2014
DOI: 10.1097/wnr.0000000000000105
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TRPV1 in the C57BL/6 mice brain hippocampus and cortex during development

Abstract: Transient receptor potential vanilloid 1 (TRPV1) channel has been found to be expressed in a variety of tissues over the last few years, including the central nervous system (CNS). However, the distribution of TRPV1 in the CNS remains a controversial question. Here, we reveal that the expression of TRPV1 can be detected in the C57BL/6 mouse hippocampus and cortex using real-time PCR and western blot. Beyond that, mRNA and protein expression levels of TRPV1 show dynamic changes during brain development. Compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
5
10
0
Order By: Relevance
“…Additionally, we found a substantial increase in the mRNA expression of TRPV2 in the hippocampus of some P20 rats. In support of our findings, TRPV1 and TRPV2 transcripts have been shown to be expressed in rat hippocampal tissues and both receptors are activated by CBDV (Huang et al, 2014;Morales et al, 2017). We observed a striking, but incomplete, decrease in the anticonvulsant effect of CBDV in TRPV1 knockout mice, suggesting that increased TRPV1 expression may contribute to the developmental change in sensitivity to CBDV, and that CBDV actions may be partially TRPV1 independent.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, we found a substantial increase in the mRNA expression of TRPV2 in the hippocampus of some P20 rats. In support of our findings, TRPV1 and TRPV2 transcripts have been shown to be expressed in rat hippocampal tissues and both receptors are activated by CBDV (Huang et al, 2014;Morales et al, 2017). We observed a striking, but incomplete, decrease in the anticonvulsant effect of CBDV in TRPV1 knockout mice, suggesting that increased TRPV1 expression may contribute to the developmental change in sensitivity to CBDV, and that CBDV actions may be partially TRPV1 independent.…”
Section: Discussionsupporting
confidence: 89%
“…We obtained Trpv1 À/À mice and confirmed the absence of TRPV1 protein in their brains (Figures S1A and S1B) at 8 weeks, a peak time of TRPV1 expression in the murine brain (Huang et al, 2014). In addition, activation of TRPV1 with the specific agonist capsaicin (CAP) induced Ca 2+ influx in the DG granule cells of hippocampal slices obtained from wild-type (WT) mice, but not from Trpv1 À/À mice (Figures S1C-S1E).…”
Section: Trpv1 à/à Mice Exhibit Enhanced Basal Hippocampal Neurogenessupporting
confidence: 60%
“…Glucocorticoids rapidly stimulate EB production in the brain, whereupon EBs bind to cannabinoid receptor 1 (CB1) and transient receptor potential vanilloid 1 (TRPV1), resulting in inhibition of neurotransmitter release (Popoli et al, 2011). The TRPV1 channel, which is mainly expressed in primary sensory neurons of the dorsal root and trigeminal ganglia of the peripheral nervous system (Mezey et al, 2000), is thought to extend to many regions of the brain, including hippocampus, amygdala, and hypothalamus (Chá vez et al, 2010;Mezey et al, 2000;Cristino et al, 2006;Huang et al, 2014). TRPV1 is expressed in the subgranular zone (SGZ) of the hippocampal dentate gyrus (DG), a neurogenic region that contributes to neuroplasticity, in line with its suggested role in psychiatric disorders (Chahl, 2011;Stock et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We first assessed the presence of functional TRPV1 at neocortical synapses by applying capsaicin (10 μM), a TRPV1 agonist, and we observed that EPSCs were decreased (79.1 ± 6.2% of baseline, p < 0.05, n = 5; data not shown). This is in in agreement with the expression of TRPV1 in pyramidal cells of the rat neocortex revealed by immunoelectronmicroscopy (Tóth et al, 2005 ), real-time PCR (Huang et al, 2014 ; but see Cavanaugh et al, 2011 ) or functional (Pezzoli et al, 2014 ) analysis. We next used capsazepine, a competitive TRPV1 antagonist, and first verified that capsazepine (10 μM) had no significant effect on basal EPSCs (105.2 ± 5.5%, p = 0.3980, n = 5) in absence of paired stimulation, indicating that TRPV1 has no constitutive activity at neocortical layer 2/3 synapses.…”
Section: Resultssupporting
confidence: 85%
“…Indeed, although an immunoelectronmicroscopy study reported TRPV1 protein in neocortex at the postsynaptic dendritic spines of pyramidal cells (Tóth et al, 2005 ), a multi-approach investigation ( in situ hybridization, calcium imaging) detects TRPV1 only at the level of the arteriolar smooth muscle cells (Cavanaugh et al, 2011 ). Recent studies using real-time PCR and western blot (Huang et al, 2014 ) and patch-clamp recordings (Pezzoli et al, 2014 ) showed expression of TRPV1 by pyramidal cells of the neocortex. Here, EPSC recordings, before and after TRPV1 agonist (capsaicin) application, show a marked decrease of EPSC amplitude in presence of capsaicin, in line with previous observations (Pezzoli et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%